THE CHANGING TYPES OF SOCIAL SURVEILLANCE THROUGH GLOBALIZATION - Sarıgül, Fatma Altınbaş (PEOPLE: International Journal of Social Sciences, 2018)
Each individual takes part in social surveillance both as the watcher and the watched. The degree of watching and being watched, however, shows a substantial change as the world becomes more globalized. There are three main types of social surveillance, based on whether the space that is being watched is somewhere local, global or a cyberspace. The first type of surveillance is considered a Panopticon emerged with modernism, where a small group of people watches over a larger group of people. The second one is the Synopticon where the many watch over the few. Emerged especially with the growth of the mass media, the Synopticon is the product of a more globalized world when compared to the concept of Panopticon. The third type of surveillance is the Omnipticon, where both Panopticon and Synopticon are applied simultaneously. While the globalization has stripped a minority of the privilege of watching and conferred it on the whole of society, surveillance has gradually begun to evolve from a mean of psychological pressure into an alluring psychological desire. As the world becomes more globalized, the grip of social control becomes firmer and stronger than thought even though the physical local pressures on the individual seem to have been diminished. While it might seem liberating at first sight, the globalization also leads to an anti-emancipatory world.